(untitled) (Journal of Rangpur Medical College, 2023)
Background: The use of tobacco has been significantly increased globally in recent decades. Easy availability and the low price gives rise to high consumption of tobacco smoking. Tobacco use is a leading preventable cause of premature mortality and morbidity.. Previous studies described the detrimental effects of tobacco smoking on liver function. Objectives: To observe the effects of tobacco consumption on the levels of serum alanine aminotransferase and alkaline phosphatase levels in smokers. Methods: The cross-sectional analytical study was conducted from January 2017 to January 2018 in the department of physiology, Rangpur Medical College, Rangpur. A total number of 60 subjects were selected, among them 30 were apparently healthy non-tobacco chewer non-smoker subjects as control group ( group A) and 30 were apparently healthy smoker non-tobacco chewer subjects ( group B). The subjects were selected from different area of Rangpur city. The effects of cigarette smoking on liver function were studied by measuring the levels of serum alanine aminotransferase and alkaline phosphatase levels. For statistical analysis independent sample “t” test was performed by computer based software SPSS-17.0 version for windows. Results: Serum alanine aminotransferase and alkaline phosphatase levels were significantly higher (p<0.001) in smoker non-tobacco chewer subjects as compared with the healthy control subjects. Conclusion: The increased serum alanine aminotransferase and alkaline phosphatase levels in smoker non-tobacco chewer subjects were evidence of development of liver function impairment due to tobacco smoking and this might offer a new preventive approach to liver function impairment in population with tobacco smoking. J Rang Med Col. March 2023; Vol. 8, No. 1:65-68